What you can do for the environment - Wald, Mike 1961- (New York : Chelsea House, 1993)
Examines current environmental problems, explores possible solutions, and reviews recent environmental action and its effects.
Includes bibliographical references (p. 99-100) and index.
Keywords: Environmental protection -- Citizen participation -- Juvenile literature; Environmental protection